(x+2+3j)*(x+2-3j)=0

Simple and best practice solution for (x+2+3j)*(x+2-3j)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+2+3j)*(x+2-3j)=0 equation:


Simplifying
(x + 2 + 3j)(x + 2 + -3j) = 0

Reorder the terms:
(2 + 3j + x)(x + 2 + -3j) = 0

Reorder the terms:
(2 + 3j + x)(2 + -3j + x) = 0

Multiply (2 + 3j + x) * (2 + -3j + x)
(2(2 + -3j + x) + 3j * (2 + -3j + x) + x(2 + -3j + x)) = 0
((2 * 2 + -3j * 2 + x * 2) + 3j * (2 + -3j + x) + x(2 + -3j + x)) = 0
((4 + -6j + 2x) + 3j * (2 + -3j + x) + x(2 + -3j + x)) = 0
(4 + -6j + 2x + (2 * 3j + -3j * 3j + x * 3j) + x(2 + -3j + x)) = 0

Reorder the terms:
(4 + -6j + 2x + (6j + 3jx + -9j2) + x(2 + -3j + x)) = 0
(4 + -6j + 2x + (6j + 3jx + -9j2) + x(2 + -3j + x)) = 0
(4 + -6j + 2x + 6j + 3jx + -9j2 + (2 * x + -3j * x + x * x)) = 0

Reorder the terms:
(4 + -6j + 2x + 6j + 3jx + -9j2 + (-3jx + 2x + x2)) = 0
(4 + -6j + 2x + 6j + 3jx + -9j2 + (-3jx + 2x + x2)) = 0

Reorder the terms:
(4 + -6j + 6j + 3jx + -3jx + -9j2 + 2x + 2x + x2) = 0

Combine like terms: -6j + 6j = 0
(4 + 0 + 3jx + -3jx + -9j2 + 2x + 2x + x2) = 0
(4 + 3jx + -3jx + -9j2 + 2x + 2x + x2) = 0

Combine like terms: 3jx + -3jx = 0
(4 + 0 + -9j2 + 2x + 2x + x2) = 0
(4 + -9j2 + 2x + 2x + x2) = 0

Combine like terms: 2x + 2x = 4x
(4 + -9j2 + 4x + x2) = 0

Solving
4 + -9j2 + 4x + x2 = 0

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -9j2 + 4x + -4 + x2 = 0 + -4

Reorder the terms:
4 + -4 + -9j2 + 4x + x2 = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -9j2 + 4x + x2 = 0 + -4
-9j2 + 4x + x2 = 0 + -4

Combine like terms: 0 + -4 = -4
-9j2 + 4x + x2 = -4

Add '-4x' to each side of the equation.
-9j2 + 4x + -4x + x2 = -4 + -4x

Combine like terms: 4x + -4x = 0
-9j2 + 0 + x2 = -4 + -4x
-9j2 + x2 = -4 + -4x

Add '-1x2' to each side of the equation.
-9j2 + x2 + -1x2 = -4 + -4x + -1x2

Combine like terms: x2 + -1x2 = 0
-9j2 + 0 = -4 + -4x + -1x2
-9j2 = -4 + -4x + -1x2

Divide each side by '-9'.
j2 = 0.4444444444 + 0.4444444444x + 0.1111111111x2

Simplifying
j2 = 0.4444444444 + 0.4444444444x + 0.1111111111x2

Reorder the terms:
-0.4444444444 + j2 + -0.4444444444x + -0.1111111111x2 = 0.4444444444 + 0.4444444444x + 0.1111111111x2 + -0.4444444444 + -0.4444444444x + -0.1111111111x2

Reorder the terms:
-0.4444444444 + j2 + -0.4444444444x + -0.1111111111x2 = 0.4444444444 + -0.4444444444 + 0.4444444444x + -0.4444444444x + 0.1111111111x2 + -0.1111111111x2

Combine like terms: 0.4444444444 + -0.4444444444 = 0.0000000000
-0.4444444444 + j2 + -0.4444444444x + -0.1111111111x2 = 0.0000000000 + 0.4444444444x + -0.4444444444x + 0.1111111111x2 + -0.1111111111x2
-0.4444444444 + j2 + -0.4444444444x + -0.1111111111x2 = 0.4444444444x + -0.4444444444x + 0.1111111111x2 + -0.1111111111x2

Combine like terms: 0.4444444444x + -0.4444444444x = 0.0000000000
-0.4444444444 + j2 + -0.4444444444x + -0.1111111111x2 = 0.0000000000 + 0.1111111111x2 + -0.1111111111x2
-0.4444444444 + j2 + -0.4444444444x + -0.1111111111x2 = 0.1111111111x2 + -0.1111111111x2

Combine like terms: 0.1111111111x2 + -0.1111111111x2 = 0.0000000000
-0.4444444444 + j2 + -0.4444444444x + -0.1111111111x2 = 0.0000000000

The solution to this equation could not be determined.

See similar equations:

| t-24=15 | | F(x)=3x-2x+5 | | 12x+21=3(4c+6) | | 5x-(-1-2x)=8 | | 4x+5y=-16 | | 7(X^2+2)-X=-8X+55 | | -2(sin^2)x=3sinx+1 | | -5=4a+3 | | 4b-15=-3 | | 6+3(2r-2)-3(4r+4)-9= | | 50=10-t | | 57-p=42 | | 3y-3*6+2=0 | | 2y=8x-142 | | 11(n+5)=11 | | -7(5+5a)=210 | | x=26-12x-x^2 | | 6m-5=55 | | 4cos^2*2x=0 | | 66=6-10r | | 10-x=37 | | 3r-29=13 | | f(x)=26-12x-x^2 | | 4cos^22x=0 | | -5(4+y)= | | -pq-3pq= | | -8(2p)= | | 7=k+7+8k | | 10+9z=82 | | 4(6z)= | | 6x-2=14-x | | -3(4x+6)=28 |

Equations solver categories